The role and duties of the Age Grade System in Socio-Cultural and Community Development in the Auchi Kingdom in Nigeria - Yakubu, Suleiman (My University, 2022)
Age grade system has played significant roles in the development of the communities in Nigeria before, during and after colonialism. The paper examines the role and duties of the age grade system in the Auchi Kingdom in Etsako West Local Government Area of Edo State in Nigeria. The paper argues that the cultural bond and unity of purpose of the members of the age grades makes them a veritable tool for transformation of their community, preservation of their culture and tackling security challenges. This is because the age grades know their community more than out-siders. There are quite several socio-cultural indigenous practices such as female circumcision, idol worshipping, slavery etc. that have been abolished. The study, therefore, concludes that age grade system among the Auchi people is a system that must not be disbanded for its contributions in economic and socio-cultural spheres of the Auchi Kingdom which has remained unquantifiable.
Úloha a povinnosti systému věkových tříd v sociokulturním a komunitním rozvoji v království Auchi v Nigérii
Keywords: age grade system; community development; culture; security; tradition; systém věkových tříd; rozvoj komunity; kultura; bezpečnost; tradice